Wearable Vibrotactile Haptic Device for Stiffness Discrimination during Virtual Interactions - Maereg, Andualem Tadesse; Nagar, Atulya; Reid, David; Secco, Emanuele L. (Frontiers in Robotics and AI, 2017)
In this paper, we discuss the development of cost effective, wireless and wearable vibrotactile haptic device for stiffness perception during an interaction with virtual objects. Our experimental setup consists of haptic device with five vibrotactile actuators, virtual reality environment tailored in Unity 3D integrating the Oculus Rift Head Mounted Display(HMD) and the Leap Motion controller.The virtual environment is able to capture touch inputs from users. Interaction forces are then rendered at 500Hz and fed back to the wearable setup stimulating fingertips with ERM vibrotactile actuators. Amplitude and frequency of vibrations are modulated proportionally to the interaction force to simulate the stiffness of a virtual object. A quantitative and qualitative study is done to compare the discrimination of stiffness on virtual linear spring in three sensory modalities: visual only feedback, tactile only feedback and their combination. A common psychophysics method called the Two Alternative Forced Choice (2AFC) approach is used for quantitative analysis using Just Noticeable Difference(JND) and Weber Fractions(WF). According to the psychometric experiment result, average Weber fraction values of 0.39 for visual only feedback was improved to 0.25 by adding the tactile feedback.